Keterbukaan Informasi Sebagai Mitigasi Risiko Peer To Peer Lending (Perbandingan Antara Indonesia Dan Amerika Serikat) - Inda Rahadiyan; Nikmah Mentari (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The development of peer to peer lending (P2PL) in Indonesia will always be followed by the formation of the latest regulations. However, the existing regulations do not sufficiently regulate the disclosure of information. On the other hand, in the United States as the country with the largest P2PL, information disclosure is a major part in the implementation of P2PL. The approaches used in this research are a conceptual approach, a statutory approach, and a comparative law approach. The results conclude that obtained are that the regulation regarding P2PL does have an obligation to disclose information, but the regulation is not comprehensive because it is exclusive and limited. In fact, the disclosure of information can be a part of risk mitigation in P2PL, for example, minimizing the risk of problem loans. Meanwhile, in the United States, through the Security Exchange Commission (SEC) and the Consumer Financial Protection Bureau (CFPB), detailed and periodic information disclosure is available. So that both prospective borrowers and potential lenders can consider the risks and capabilities of each party more before making transactions in P2PL. This then can be one of the risk mitigation for P2PL in the United States.